(untitled) (World Bulletin of Management and Law, 2024)
This study examines the communicative and pragmatic characteristics of diplomatic discourse, emphasizing its role in fostering international cooperation and maintaining balance in global relations. The research uses a qualitative discourse analysis framework to explore politeness strategies, hedging, and metaphorical language in official diplomatic communications. Results indicate that pragmatic elements play a vital role in achieving clarity, neutrality, and sensitivity within complex political contexts. The findings provide significant insights into how diplomatic discourse adapts to the demands of globalization and evolving communication technologies.